They Cannot, They Will Not, or We Are Asking the Wrong Questions: Re-examining Age-Related Decline in Social Cognition - Hamilton, Lucas J.; Gourley, Amy N.; Krendl, Anne C. (Frontiers in Psychology, 2022)
Social cognition is critical for successfully navigating social relationships. Current evidence suggests that older adults exhibit poorer performance in several core social-cognitive domains compared to younger adults. Neurocognitive decline is commonly discussed as one of the key arbiters of age-related decline in social-cognitive abilities. While evidence supports this notion, age effects are likely attributable to multiple factors. This paper aims to recontextualize past evidence by focusing issues of motivation, task design, and representative samples. In light of these issues, we identify directions for future research to aide our understanding of social-cognitive aging.